To find the equation of the linear function that passes through the points (-9, 1) and (-7, 3), we can use the point-slope form of a linear equation:
y - y1 = m(x - x1)
First, we need to find the slope (m) using the given points:
m = (3 - 1) / (-7 - (-9))
m = 2 / 2
m = 1
Now that we have the slope (m = 1), we can choose either point to plug into the formula. Let's use point (-9, 1):
y - 1 = 1(x - (-9))
y - 1 = x + 9
Now, rearrange the equation to the standard form of a linear equation (y = mx + b):
y = x + 10
Therefore, the equation of the linear function that passes through the points (-9, 1) and (-7, 3) is y = x + 10.
Write the equation of the linear function that passes through the points ( − 9 1) and ( − 7 3).
1 answer